3D time‐domain nonlinear analysis of soil‐structure systems subjected to obliquely incident SV waves in layered soil media. (7th March 2021) - Zhang, Wenyang; Taciroglu, Ertugrul
Abstract: Numerous experiments and prior analyses have confirmed that the angle of incidence of a seismic wave can significantly affect ground response and dynamic soil–structure interaction (SSI) behavior. Realistically, obliquely incident waves will be generated due to the soil heterogeneity and stratigraphy, which can lead into complex wave propagation and scattering patterns. In this study, we propose a novel methodology that (i) utilizes the wave potential theory to derive the 3D time‐domain analytical solutions for free‐field response under obliquely incident SV waves in layered soil media; (ii) makes use of high‐fidelity numerical tools—namely, the domain reduction method (DRM) and the perfectly matched layers (PMLs)—to inject the obliquely incident waves into the domain of interest and to absorb the outgoing scattered motions, respectively; (iii) enables nonlinear time‐domain site response and SSI analyses that feature an advanced constitutive model for soil. Finally, a 3D 20‐story steel building is modeled as a case study. The building rests on a two‐layer half‐space and is subjected to an obliquely incident seismic wave. The SV wave's angles of incidence are varied to investigate its effects on structural responses, such as horizontal, vertical, and rotational floor accelerations, as well as interstory drift ratios.